2006
DOI: 10.7326/0003-4819-145-2-200607180-00008
|View full text |Cite
|
Sign up to set email alerts
|

The Association between Quality of Care and the Intensity of Diabetes Disease Management Programs

Abstract: Disease management strategies were associated with better processes of diabetes care but not with improved intermediate outcomes or level of medication management. A greater focus on direct measurement, feedback, and reporting of intermediate outcome levels or of level of medication management may enhance the effectiveness of these programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
85
1
2

Year Published

2006
2006
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 124 publications
(93 citation statements)
references
References 28 publications
5
85
1
2
Order By: Relevance
“…Factors related to processes of care, • Resources to support providers' prevention interventions (print or other materials, skilled support staff, cost-efficient intervention formats, office systems, community partnerships) (29). Limited resources for dietary and physical activity counseling.…”
Section: Constructs Explored Findingsmentioning
confidence: 99%
“…Factors related to processes of care, • Resources to support providers' prevention interventions (print or other materials, skilled support staff, cost-efficient intervention formats, office systems, community partnerships) (29). Limited resources for dietary and physical activity counseling.…”
Section: Constructs Explored Findingsmentioning
confidence: 99%
“…M a n y d i a b e t e s intervention studies are limited by inadequate sample size, nonrandomized patients and clinics, lack of control subjects, or limited scope of implementation within a single medical group or health system (11,13,14). Although some trials of quality improvement strategies have demonstrated small improvements in the process of care delivery, demonstrating improvement in control of A1C, LDL, and systolic blood pressure (SBP) has been more challenging (15)(16)(17)(18). The paucity of effective interventions improving diabetes care in primary care settings led us to design a "practical clinical trial" to test whether implementation of an organizational intervention could improve both diabetes care processes and clinical outcomes in primary care (19).…”
mentioning
confidence: 99%
“…(11). The primary objective of the TRIAD Study is to determine how the structural and organizational characteristics of health systems and health care provider groups influence processes and outcomes of diabetes care (12). Six translational research centers collaborate with 10 health plans and 68 provider groups, which serve ϳ180,000 patients with diabetes.…”
mentioning
confidence: 99%